2014
DOI: 10.3390/ijms15069594
|View full text |Cite
|
Sign up to set email alerts
|

NOD-Like Receptors in Intestinal Homeostasis and Epithelial Tissue Repair

Abstract: The intestinal epithelium constitutes a dynamic physical barrier segregating the luminal content from the underlying mucosal tissue. Following injury, the epithelial integrity is restored by rapid migration of intestinal epithelial cells (IECs) across the denuded area in a process known as wound healing. Hence, through a sequence of events involving restitution, proliferation and differentiation of IECs the gap is resealed and homeostasis reestablished. Relapsing damage followed by healing of the inflamed muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 291 publications
0
39
0
Order By: Relevance
“…However, MUC2 is also significantly upregulated for C3H Conv C1200 and 129 ASF C600 groups. Thus, upregulated signaling of MUC2 could be due to goblet cells in organoids somehow sensing the disruption, and are preparing for reparation and protection of the epithelial cells (Parlato & Yeretssian, ). From Parlato and Yeretssian () a signal transduction pathway involving MUC2 and NF‐kB for intestinal epithelial tissue repair has been mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, MUC2 is also significantly upregulated for C3H Conv C1200 and 129 ASF C600 groups. Thus, upregulated signaling of MUC2 could be due to goblet cells in organoids somehow sensing the disruption, and are preparing for reparation and protection of the epithelial cells (Parlato & Yeretssian, ). From Parlato and Yeretssian () a signal transduction pathway involving MUC2 and NF‐kB for intestinal epithelial tissue repair has been mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune receptors, pattern recognition receptors (PRRs), are the key factors to trigger the inflammatory response [5]. In addition to regulating inflammation development, some PRRs also play an important role in the process of cell proliferation and apoptosis [6]. These receptors mainly include Toll like receptors (TLRs), Nod-like receptor (NLRs), RIG-I like receptor (RLRs), AIM2 like receptor (ALRs), and C-type lectin receptor (CLRs).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, NLRP3 and NLRC4 sense a variety of enteric pathogens and pathobionts and initiate immune responses against these pathogens. 7, 8, 9 In addition, several ASC-containing inflammasomes are involved in the maintenance of intestinal homeostasis and the prevention of dysbiosis; consequently, they are also involved in the pathology of IBD and colitis-linked colorectal cancer. 3, 4, 10 Initial studies suggested that inflammasome activation and the production of downstream effectors is detrimental for colitis.…”
Section: Introductionmentioning
confidence: 99%